2021
DOI: 10.1186/s12302-021-00480-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of cadmium in rice roots based on LIBS and chemometrics methods

Abstract: Background Excessive cadmium can damage cell structure, inhibit enzyme activity, and affect metabolic process, thus, leading to decline of rice yield and quality. Root is an important organ of crops, the detection of cadmium in root is essential for limitation of cadmium in rice grains. Results In this study, laser-induced breakdown spectroscopy (LIBS) was applied for cadmium quantitative analysis. Pretreatment methods, including median absolute de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…LIBS has been applied for sorting wood waste [40] and, recently, for classifying wood species [41]. Some studies of the application of LIBS on plant roots can be found in the literature focused mainly on the characterization of elemental composition [42][43][44][45][46]. However, to the best of our knowledge, there are no studies in the literature trying to relate the biochemical structure and composition of roots with shallow landslide occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…LIBS has been applied for sorting wood waste [40] and, recently, for classifying wood species [41]. Some studies of the application of LIBS on plant roots can be found in the literature focused mainly on the characterization of elemental composition [42][43][44][45][46]. However, to the best of our knowledge, there are no studies in the literature trying to relate the biochemical structure and composition of roots with shallow landslide occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Decision tree (DT), support vector regression (SVR) and radial basis function neural network (RBFNN) have a strong ability to deal with nonlinear issues. These methods combined with spectral technology have achieved good results in detection of crop diseases [37], determination of crop origins [38,39] and prediction of physiological indexes [40,41]. It confirms the superiority of machine learning in mining the relationship between variables.…”
Section: Introductionmentioning
confidence: 61%
“…In another paper, Guo et al [125] demonstrated that LIBS with PLSR modeling has better prediction performance and lower LoD (1079 ppm) than Raman and FT-IR with PLSR. In a similar study, Wang et al [127] applied LIBS and the chemometrics method to determine the cadmium content in rice roots. Tian et al [128] used the LIBS system with machine learning to evaluate the phosphorous concentration in seafood, and the LoD was estimated to be around 370 ppm for normalized data.…”
Section: Analysis Of Foodsmentioning
confidence: 99%
“…To enhance accuracy in the detection of heavy metals in mulberry leaves, Yang et al [150] proposed a novel analysis framework consisting of a self-organizing map (SOM), successive projection algorithm (SPA), and uninformative variable elimination (UVE). LIBS was combined with chemometrics for quick and accurate quantitative analysis of heavy metal Cd in rice stems [151] and roots [127]. Table 4 summarizes the different works related to detecting nutrients and toxic elements in plants by LIBS.…”
Section: Micro-and Macronutrients Detection In Plantsmentioning
confidence: 99%